Analisis Pesan dan Persepsi Konsumen terhadap Iklan TV Aqua Pasca Boikot Produk Terafiliasi Israel - Prastari, Aprilina; Gaib, Wafa Auliya Insan (Jurnal Audiens, 2025)
The Israeli occupation of Palestine has been ongoing since 1948. After decades of military aggression, tensions escalated in October 2023 and continued up to the time of this article's writing in March 2025—marking over a year of brutal attacks. One of the major protest movements that gained momentum since October 2023 has been the boycott of brands affiliated with Israel. One such brand is Aqua, a bottled water product whose producer, Danone, is affiliated with Israel. In response to the widespread boycott, Aqua released a "100% Indonesia" TV commercial across television and digital platforms like YouTube. In addition to message analysis, this study aims to understand consumer perceptions of Aqua’s "100% Indonesia" Television Commercial (TVC) and how it influences their decision to continue or discontinue the boycott. A questionnaire was distributed across several groups consisting of Muslims concerned with the Palestinian cause. The results show that consumers with strong religious understanding, who actively follow news about Palestine and participate in pro-Palestine actions, are highly committed to expressing solidarity, one way being through boycotting brands affiliated with the occupiers. Any advertisement, no matter how well-crafted or clearly messaged, will not alter the attitudes and commitments they have made, especially when the product has many available substitutes.